SIMULATION OF ELECTRO-THERMAL CONDITION IN A FAULTY LOW-CURRENT CONTACT (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
It has been suggested in earlier works of literature that the accuracy of the thermal simulation of electrical connectors is closely related to contact resistance. Contact resistance in electrical connectors occurs as a result of both constriction resistance (caused by narrow paths in which the current flows through the electrical connector) and film resistance (oxidized metals caused by the high resistivity of materials and impurities from the atmosphere etc.). This paper reviews the oxidation and wear affecting electrical connectors by proposing a thermal-electrical coupled finite element simulation (FEM) of the contact temperature rise of a simple contact model in COMSOL Multiphysics.
Keywords: Contact resistance; FEM; Electric connectors; Electric rezistance; Low Current; Comsol Multiphysics